A Randomized Impact Evaluation of a Tuition-Free Private School Targeting Low Income Students in Uruguay. Issue 1 (1st May 2016) - Balsa, Ana Inés; Cid, Alejandro
Abstract : Using a randomized trial, we evaluate the impact of Liceo Jubilar, a tuition-free private school providing middle school education to poor students in Montevideo, Uruguay. The research compares adolescents randomly selected to enter the school with those not drawn in the school lottery. Several features of this school — the capacity to select personnel, a culture of high expectations, a safe and disciplined environment, differential teaching, extended instructional time, strong parental involvement, and a rich offer of extracurricular activities — contrast with the country's highly centralized public education system. We find large positive impacts of Liceo Jubilar on students' promotion rates and academic expectations. Our results shed light on new approaches to education that may contribute to improve opportunities for disadvantaged adolescents in developing countries.